The Effectiveness of AI-Integrated Genre-Based Materials in Enhancing Creative Thinking in EFL Procedural Text Writing - Miesmiarini, Moeria Erry; Senowarsito, Senowarsito; Sodiq, Jafar (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study responds to the growing need for pedagogically grounded integration of artificial intelligence in EFL writing instruction, particularly in fostering students’ creative thinking in procedure text writing. While AI has been increasingly utilized in language learning, its systematic integration with Genre-Based Instruction remains insufficiently explored. Therefore, this study aims to develop and evaluate AI-integrated genre-based instructional materials, namely GRAMCHAT-QUIZ, to enhance students’ creative thinking. This study employed a Research and Development (R&D) design utilizing the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants involved tenth-grade students and an English teacher at a senior high school in Central Java, Indonesia. Data were collected through questionnaires, interviews, classroom observation, expert validation, and students’ writing products. The data were analyzed qualitatively to examine students’ creative thinking in terms of fluency, flexibility, and elaboration. The findings reveal that the developed materials are valid and feasible based on expert validation results. Classroom implementation indicates that the integration of AI supports students in generating ideas, employing varied language expressions, and elaborating their writing more effectively. In addition, students demonstrate positive responses and increased engagement during the learning process. In conclusion, AI-integrated genre-based materials show potential in enhancing students’ creative thinking in EFL procedure text writing. The study implies that teachers can meaningfully integrate AI within structured genre-based instruction to support students’ creativity, engagement, and writing development.